Force-generating capacities and fatigability of the quadriceps femoris in relation to different exercise modes - Ullrich, B.; Brüggemann, G. P. (The Journal of Strength and Conditioning Research, 2008)
In this study, we examined whether different exercise modes provoke functional differences in maximal and explosive force-generating capacities and fatigability of the quadriceps femoris (QF). Additionally, the interaction of different functional capacities was studied in competitive athletes. Ten competitive tennis players and 10 endurance athletes participated in the study. Pre-exercise force-generating capacities were determined during maximal voluntary isometric knee extensions (MVC). Fatigability of the QF was studied using sustained isometric contractions with target loads of 20% and 40% of pre-exercise MVC. Postexercise MVCs were conducted 20 seconds, 1 minute, and 3 minutes post task failure. Muscle activation of the QF during the fatiguing exercises and postexercise MVCs was estimated using surface electromyography. Higher explosive force-generating capacities, but no differences in absolute moments, were detected in tennis players compared with endurance athletes. Fatigability of the QF during both fatiguing tasks was approximately the same in both athletic populations. This was indicated by minor group differences in endurance time, postexercise MVC production, and electromyography (EMG)-estimated muscle activation during fatigue. Variability in endurance time was not significantly associated with pre-exercise force-generating capacities in these competitive athletes. In both athletic populations, recovery of MVC was significantly slower after the fatiguing contraction with 20% of MVC compared with that with 40% of MVC. These results may enhance understanding of plasticity of the neuromuscular system and yield interesting information for the optimization of athletic training programs. Explosive strength training might enhance endurance athletes' explosiveness without decreasing muscle fatigue resistance. The exercise profile of competitive tennis is suggested to act as a sufficient trigger to reach high neuromuscular fatigue resistance but may be inadequate to cause significant gains in absolute muscle strength.